Rolling up transition metal dichalcogenide nanoscrolls via one drop of ethanol - Xueping Cui (Nature Portfolio, 2018)
Nanoscrolls (NSs) have interesting properties due to papyrus-like rolled-up geometry but their synthesis is difficult. Here Cui et al. show that vapor deposited monolayer transition metal dichalcogenide flakes form patternable arrays of NSs with the assistance of one droplet of ethanol solution.